Automation Model of Cosplay Costumes Using Rapid Prototyping Approach - Kurnia Akbar; Paputungan, Irving V (International Journal of Informatics and Computation, 2026)
This study proposes an Internet of Things (IoT)-enabled cosplay costume developed using a rapid prototyping approach to enhance interactivity and visual performance. The system integrates programmable LED lighting, motion sensors, and audio modules to create dynamic responses during cosplay presentations. The prototype evaluation demonstrates that interactive costume features significantly improve audience engagement and user satisfaction. In particular, 65% of participants report greater engagement when costume colors can be controlled through mobile applications, while 70% express higher satisfaction with motion-sensitive and audio-responsive effects. The results also reveal several practical challenges related to the implementation of wearable electronic systems in costume design. The production cost of the IoT-enabled costume increases by approximately 30–50% compared with conventional costume fabrication. In addition, around 80% of users report discomfort due to the additional weight of electronic components and battery systems. These findings indicate that while interactive technologies improve performance and audience experience, ergonomic design and power management remain important considerations. Overall, this study demonstrates that integrating rapid prototyping and wearable IoT technologies can transform traditional cosplay costumes into interactive smart fashion systems. The proposed approach provides a foundation for automated and technologically enhanced costume production, while also highlighting the need for further improvements in lightweight electronics and energy efficiency to support practical and comfortable wearable implementations.